2003
DOI: 10.1103/physrevc.67.054603
|View full text |Cite
|
Sign up to set email alerts
|

Fusion cross sections at deep sub-barrier energies

Abstract: A recent publication reports that heavy-ion fusion cross sections at extreme subbarrier energies show a continuous change of their logarithmic slope with decreasing energy, resulting in a much steeper excitation function compared with theoretical predictions. We show that the energy dependence of this slope is partly due to the asymmetric shape of the Coulomb barrier, that is its deviation from a harmonic shape. We also point out that the large low-energy slope is consistent with the surprisingly large surface… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
77
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 22 publications
7
77
0
3
Order By: Relevance
“…It was observed that a wide range of values from 0.65 a fm  to fm a 5 . 1  of diffuseness parameter are required to describe various nuclear phenomena [5][6][7][8][9][10][11][12]. As the value of diffuseness parameter increases beyond 0.65 a fm  , the potential pocket becomes more and more shallow and disappears for large values and the fusion barrier radius decreases rapidly [6,[13][14][15].…”
mentioning
confidence: 99%
“…It was observed that a wide range of values from 0.65 a fm  to fm a 5 . 1  of diffuseness parameter are required to describe various nuclear phenomena [5][6][7][8][9][10][11][12]. As the value of diffuseness parameter increases beyond 0.65 a fm  , the potential pocket becomes more and more shallow and disappears for large values and the fusion barrier radius decreases rapidly [6,[13][14][15].…”
mentioning
confidence: 99%
“…For instance, it has been a long-standing problem that a standard value of a ∼ 0.63 fm for the surface diffuseness parameter of the real nuclear potential appears too small to account for fusion data, even though this value is required to fit scattering data [12,13]. This problem is also related [14][15][16] to the deviations of fusion cross sections at deep subbarrier energies from the predictions of standard coupled-channels calculations [17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…The agreement between the calculation and the experimental data is reasonable both for the fusion and the quasi-elastic barrier distributions. For the fusion barrier distribution D fus , the agreement will be further improved if one uses a larger value of diffuseness parameter a [5,27] (see the dotted line). Fig.…”
Section: Barrier Distribution For Multi-channel Systemsmentioning
confidence: 99%